The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/infdis/jiu662
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Influenza Can Poise Hosts for CD4 T-Cell Immunity to H7N9 Avian Influenza

Abstract: The emergence of avian H7N9 viruses has raised concerns about its pandemic potential and prompted vaccine trials. At present, it is unknown whether there will be sufficient cross-reactive hemagglutinin (HA)-specific CD4 T-cell memory with seasonal influenza to facilitate antibody production to H7 HA. There has also been speculation that H7N9 will have few CD4 T-cell epitopes. In this study, we quantified the potential of seasonal influenza to provide memory CD4 T cells that can cross-reactively recognize H7 HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 42 publications
0
44
0
1
Order By: Relevance
“…Confirmation that this epitope is recognized in human CD4 T cells elicited by seasonal influenza was provided by Kwok and co-workers using HLA-DR1 tetramers (64). We have also obtained strong evidence that CD4 T cells generated by seasonal influenza can cross react with H7-derived peptides (62). In these studies, 17-mer peptides representing the most highly conserved segments of H7 HA relative to its closest seasonal strain (H3) were identified and tested.…”
Section: The Availability Of Ha-specific Cd4 T Cells For Responses Tomentioning
confidence: 96%
See 1 more Smart Citation
“…Confirmation that this epitope is recognized in human CD4 T cells elicited by seasonal influenza was provided by Kwok and co-workers using HLA-DR1 tetramers (64). We have also obtained strong evidence that CD4 T cells generated by seasonal influenza can cross react with H7-derived peptides (62). In these studies, 17-mer peptides representing the most highly conserved segments of H7 HA relative to its closest seasonal strain (H3) were identified and tested.…”
Section: The Availability Of Ha-specific Cd4 T Cells For Responses Tomentioning
confidence: 96%
“…There is a growing appreciation that vaccine strategies that more fully engage the cellular response can enhance protection. A number of recent studies have sought to quantify and characterize the repertoire of circulating memory CD4 T cells with specificity towards influenza antigens (59, 60, 62, 63, 8387). Many studies by other groups have concluded that the most prominent influenza-reactive CD4 T cells are those specific for internal virion proteins, particularly M1 and NP (8486), as well as HA (63).…”
Section: Human Memory Cd4 T Cells Reactive To Influenza Virusmentioning
confidence: 99%
“…We suspect that the major mechanism that underlies poor responses of humans to avian vaccines is simply a low abundance of memory helper CD4 T cells that are recruited into the response. In our studies on CD4 T cell reactivity to H7 HA-derived epitopes in humans that have never encountered H7 avian viruses or vaccines, we have found that cross-reactivity is detectable in many but is of relatively low abundance for most individuals (24). In contrast, memory CD4 T cells specific for seasonal H1N1-and H3N2-derived HA proteins are readily detectable in humans (25,26).…”
Section: Discussionmentioning
confidence: 81%
“…A strong correlation between neutralizing antibody responses following TIV vaccination and the expansion of a circulating CD4+ T-cell population with a Tfh-like phenotype has been reported [140,141]. Furthermore, broadly cross-reactive memory CD4+ T cells capable of recognizing antigenic shift variants can be primed by seasonal influenza exposure [142][143][144]. This population of HA-specific CD4+ memory cells may constitute an expanded pool of Tfh to provide cognate help for HAbinding B cells to subsequent immunization.…”
Section: Uiv Targeting Other Viral Proteinsmentioning
confidence: 95%